Autophagy-Related Proteins Target Ubiquitin-Free Mycobacterial Compartment to Promote Killing in Macrophages - Bah, Aïcha; Lacarrière, Camille; Vergne, Isabelle (Frontiers in Cellular and Infection Microbiology, 2016)
Autophagy is a lysosomal degradative process that plays essential functions in innate immunity, particularly, in the clearance of intracellular bacteria such as M.tuberculosis. The molecular mechanisms involved in autophagy activation and targeting of mycobacteria, in innate immune responses of macrophages, are only partially characterized. Autophagy targets pathogenic Mycobacterium tuberculosis via a cytosolic DNA recognition- and an ubiquitin-dependent pathway. In this report, we show that non-pathogenic M.smegmatis induces a robust autophagic response in THP-1 macrophages with an upregulation of several autophagy-related genes. Autophagy activation relies in part on recognition of mycobacteria by Toll-like receptor 2 (TLR2). Notably, LC3 targeting of M.smegmatis does not rely on membrane damage, ubiquitination or autophagy receptor recruitment. Lastly, M.smegmatis promotes recruitment of several autophagy proteins which are required for mycobacterial killing. In conclusion, our study uncovered an alternative autophagic pathway triggered by mycobacteria which involves cell surface recognition but not bacterial ubiquitination.